Pseudolaguvia nubila, a new sisorid catfish (Teleostei: Sisoridae) from northeastern India - Ng, Heok Hee; -, Lalramliana; Lalronunga, Samuel; -, Lalnuntluanga (Zootaxa, 2013)
This study describes Pseudolaguvia nubila, a new miniature sisorid catfish from the Kaladan River drainage in northeast-ern India. Pseudolaguvia nubila can be distinguished from congeners in having a combination of a mottled brown body with yellowish bands, a weakly projecting snout in which the premaxillary teeth are barely exposed when the mouth is closed, head width 19.7–21.7% standard length (SL), eye diameter 10.8–14.0% head length (HL), interorbital distance 25.6–31.8% HL, absence of a pale Y-shaped marking on the dorsal surface of the head and supraoccipital process, a smooth anterior edge of the dorsal spine, dorsal-fin spine length 16.4–19.3% SL, length of dorsal-fin base 15.1–17.3% SL, 7–8 serrations on the anterior edge of the pectoral spine, pectoral-fin spine length 18.1–22.0% SL, dorsal to adipose distance 13.1–16.8% SL, length of adipose-fin base 14.2–15.9% SL, pelvic-fin length 15.8–18.5% SL, body depth at anus 13.9–17.1% SL, caudal-peduncle length 15.7–20.2% SL, caudal-peduncle depth 9.1–11.1% SL, and caudal-fin length 20.3–25.3% SL.